Anterior Cruciate Ligament Retensioning—A Novel Revision Procedure Using Suture Augmentation: A Case Report With A 3-Year Follow-up. Issue 2 (2020) - Shu, Henry T.; Day, Jonathan; Bodendorfer, Blake M.; Argintar, Evan H.
Abstract : Case: We report the case of a 44-year-old woman with previous anterior cruciate ligament (ACL) reconstruction 25 years ago in the right knee, who sustained a bucket-handle medial meniscus tear after pain and instability while pivoting during tennis. Magnetic resonance imaging demonstrated an intact but vertical and anterior ACL graft. A novel ACL retensioning procedure with suture augmentation (SA) was performed as the revision procedure. Excellent clinical outcomes and knee stability were obtained at both 17 and 36 months postoperatively. Conclusions: In certain cases, ACL retensioning with SA may be performed as the revision procedure for unsuccessful primary ACL reconstruction.